2021
DOI: 10.3390/molecules26123741
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Harvest Conditions and Host Tree Species on Chemical Composition and Antioxidant Activity of Extracts from Viscum album L.

Abstract: The content of plant secondary metabolites is not stable, and factors such as the region/location effect and seasonal variations have an impact on their chemical composition, especially in parasitic plants. Research in this area is an important step in the development of quality parameter standards of medicinal plants and their finished products. The effects of the time and place of harvest and the host tree species on the chemical composition and antioxidant activity of mistletoe extracts were investigated. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 38 publications
5
39
0
Order By: Relevance
“…Several chemical and pharmacological studies have identified various types of compounds in mistletoe, such as lectins, viscotoxins, lignans, amines, flavonoids, and polysaccharides [8,9]. Among them, flavonoids and phenolic acids are natural antioxidants involved in the biological activity of the plant and used in the prevention of diseases such as cancer, caused by oxidative stress induced by free radicals in the body [10][11][12][13]. Cancer therapy is one of the most important uses of mistletoe, proving to have beneficial effects on various types of cancer such as breast [14,15], pancreatic [16], laryngeal [17] bladder [18], or leukemia [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several chemical and pharmacological studies have identified various types of compounds in mistletoe, such as lectins, viscotoxins, lignans, amines, flavonoids, and polysaccharides [8,9]. Among them, flavonoids and phenolic acids are natural antioxidants involved in the biological activity of the plant and used in the prevention of diseases such as cancer, caused by oxidative stress induced by free radicals in the body [10][11][12][13]. Cancer therapy is one of the most important uses of mistletoe, proving to have beneficial effects on various types of cancer such as breast [14,15], pancreatic [16], laryngeal [17] bladder [18], or leukemia [19].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer therapy is one of the most important uses of mistletoe, proving to have beneficial effects on various types of cancer such as breast [14,15], pancreatic [16], laryngeal [17] bladder [18], or leukemia [19]. Over time, other bioactive activities of mistletoe have been reported, such as those related to neurological disorders, antiviral, antibacterial, anti-inflammatory, antiepileptic, or immunostimulatory activities [2,11,13,20]. Due to its bioactive compounds and its beneficial effects on the human body, mistletoe has become more and more studied, developing various pharmaceutical formulations (Iscador, Isorel, Iscucin, Lektinol, Eurixor, Helixor, Abnoba-Viscum and recombinant lectin ML -1) [13,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of phenolic compounds may vary depending on biotic (bacteria, fungi, parasites, predators) and abiotic (water, light, salts, chemicals, temperature, humidity, geographical variations, etc.) factors, the growth stage, and the part of the plant [25,26]. In the case of hemiparasites, another variable is added: the host.…”
Section: Discussionmentioning
confidence: 99%
“…This area belongs to the Northwest region, namely the Puna and is dry with a great temperature oscillation and mostly cold with subzero temperatures at night. It has been suggested that the phytochemical profile of mistletoes depends on the host of this parasitic plant [26]. However, the analysis of these combined findings strongly suggests that, from a qualitative perspective, L. cuneifolia FL fingerprint is highly conserved among geographical regions, climate conditions, and host families.…”
Section: Discussionmentioning
confidence: 99%